Management practices to mitigate the impact of high temperature on wheat - Kajal, Mamta; Yadav, Vinaya Kumar; Chhokar, Rajender Singh; Sharma, Ramesh Kumar (Journal of Cereal Research, 2025)
The changing climate is one of the biggest threats to agriculture during the years ahead. The projected changes estimated using various models in solar radiation, precipitation variability, relative humidity and CO2 concentration may result in greater temperature and water stresses to be experienced during the Rabi season when the wheat is grown. These changes in the climate could strongly affect the wheat production worldwide. Increasing temperature during grain filling stage of wheat causes substantial reduction in grain yield. This paper discusses the impact of high temperature on wheat productivity and various agronomic management practices, like time of sowing, different tillage options with or without residue retention, water management, and foliar spray of KNO3, KCl ,Urea and GA3 etc., to mitigate the high temperature stress. The delay in sowing beyond the optimum seeding time shortens the vegetative and reproductive phases. Adjustment in sowing time is one of the most important agronomic strategies to counteract the adverse effect of temperature stress. Further No-till sowing with surface residue retention helps in temperature moderation and moisture conservation which favours better crop growth and ultimately the higher crop productivity. High temperature during grain filling stage leads to forced maturity resulting in shriveled grains and thereby reduction in the grain yield.